MRI for local staging of endometrial carcinoma: Is endovenous contrast medium administration still needed?. Issue 2 (February 2015) - Bonatti, Matteo; Stuefer, Josef; Oberhofer, Nadia; Negri, Giovanni; Tagliaferri, Tiziana; Schifferle, Günther; Messini, Sergio; Manfredi, Riccardo; Bonatti, Giampietro
Highlights: Intravenous contrast material administration is not routinely indicated for MRI local staging of endometrial carcinoma. The combination of T2-weighted images with diffusion-weighted images warrants at least the same accuracy as the combination of T2-weighted images with contrast-enhanced T1-weighted images in recognizing deep myometrial invasion and cervical stromal infiltration by endometrial carcinoma. Abstract: Purpose: To compare the diagnostic performance of T2-weighted images (T2-WI) + contrast-enhanced T1-weighted images (CE T1-WI) with the one of T2-WI + diffusion-weighted images (DWI) in the assessment of myometrial and cervical stromal infiltration by endometrial carcinoma (EC). Materials and methods: Institutional review board approved our retrospective study; requirement for informed consent was waived. 56 patients with histologically proven EC who underwent preoperative MRI and surgery at our Institution over a 34 months period were included. Two radiologists independently evaluated T2-WI + CE T1-WI and T2-WI + DWI of each patient. Confidence in imaging evaluation (0–3), depth of myometrial invasion (</≥50%) and presence of cervical stromal infiltration (Yes/No) were assessed. MRI findings were compared with pathological ones. Results: Confidence in imaging evaluation was higher for T2-WI + CE T1-WI (2.83/3) than for T2-WI + DWI (2.62/3). T2-WI + DWI showed a better diagnostic performance than T2-WI + CE T1-WI in recognizing deep myometrial infiltration by EC (accuracy, sensitivity and specificity of 0.89, 0.89 and 0.89 vs. 0.86, 0.84, 0.86; p  > 0.05) whereas both imaging sequences combinations showed the same diagnostic performance in recognizing cervical stromal infiltration (accuracy, sensitivity and specificity of 0.95, 0.98 and 0.80, p  > 0.05). Conclusion: T2-WI + DWI can reliably replace the "classical" combination T2-WI + CE T1-WI for local staging of endometrial carcinoma.